2017
DOI: 10.1152/ajplung.00154.2017
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 2 and 4 have Opposing Roles in the Pathogenesis of Cigarette Smoke-induced Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is the third leading cause of morbidity and death and imposes major socioeconomic burdens globally. It is a progressive and disabling condition that severely impairs breathing and lung function. There is a lack of effective treatments for COPD, which is a direct consequence of the poor understanding of the underlying mechanisms involved in driving the pathogenesis of the disease. Toll-like receptor (TLR)2 and TLR4 are implicated in chronic respiratory diseases, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 45 publications
(108 citation statements)
references
References 111 publications
10
96
1
1
Order By: Relevance
“…[18][19][20][21][22][23] As expected, chronic CS exposure of wild-type mice increased collagen deposition around the airways compared to normal air-exposed wild-type controls (Figure 3a). [18][19][20][21][22][23] As expected, chronic CS exposure of wild-type mice increased collagen deposition around the airways compared to normal air-exposed wild-type controls (Figure 3a).…”
Section: Chronic Cs-induced Pulmonary Inflammation Is Reduced In Ttpsupporting
confidence: 73%
See 4 more Smart Citations
“…[18][19][20][21][22][23] As expected, chronic CS exposure of wild-type mice increased collagen deposition around the airways compared to normal air-exposed wild-type controls (Figure 3a). [18][19][20][21][22][23] As expected, chronic CS exposure of wild-type mice increased collagen deposition around the airways compared to normal air-exposed wild-type controls (Figure 3a).…”
Section: Chronic Cs-induced Pulmonary Inflammation Is Reduced In Ttpsupporting
confidence: 73%
“…We previously showed that mice develop small airway remodelling characterised by increases in collagen deposition, epithelial cell area and numbers of nuclei around and in the small airways in experimental COPD. [18][19][20][21][22][23] As expected, chronic CS exposure of wild-type mice increased collagen deposition around the airways compared to normal air-exposed wild-type controls (Figure 3a). CS-exposed Zfp36 aa/aa mice were protected against collagen deposition with no differences compared to normal air-exposed Zfp36 aa/aa controls and had significantly reduced deposition compared to CS-exposed wild-type controls.…”
Section: Chronic Cs-induced Pulmonary Inflammation Is Reduced In Ttpsupporting
confidence: 73%
See 3 more Smart Citations